Low cardiac output thyroid storm in a girl with Graves’ disease - Marut Chantra (2018)
© 2016 Japan Pediatric Society A 15-year-old girl with Graves’ disease presented with hypotension after methimazole and propranolol were re-started for hyperthyroidism. She was found to have pulmonary artery hypertension resulting in obstructive shock. Thyroid storm was diagnosed according to Burch and Wartofsky score. She was promptly treated with anti-thyroid drugs, inorganic iodide, corticosteroid, and respiratory support. Pulmonary hypertension was treated with inhaled nitric oxide until the clinical status improved. Propranolol was withdrawn due to poor cardiac function. We herein present a unique case of a difficult-to-treat Graves’ disease presenting with severe pulmonary hypertension resulting in low cardiac output thyroid storm.